Burkholderia pseudomallei Resistance Towards Co-trimoxazole in Sarawak : Is It a Concern? - Liana Lantong, Sumbu; Tonnii, Sia; Anand, Mohan; Mong, How Ooi; Yuwana, Podin (2024)
Burkholderia pseudomallei is inherently resistant to numerous antibiotics and is the causative agent of the potentially fatal disease, melioidosis. Co-trimoxazole is a vital antibiotic in the eradication phase of melioidosis treatment. Of late, there have been emerging reports of higher minimal inhibitory concentration readings for co-trimoxazole among B. pseudomallei clinical isolates from Sarawak, Malaysian Borneo. The objectives of this study are to determine the prevalence and to understand the mechanism of such phenomena in Sarawak. The antibiotic susceptibility of B. pseudomallei clinical isolates collected from various hospitals in the Sarawak region was assessed using disk diffusion and E-tests. The susceptibility of the isolates against trimethoprim and sulfamethoxazole was further characterised using the broth microdilution method. The MIC breakpoints were analysed according to the CLSI and EUCAST guidelines. Overall, the Sarawak clinical B. pseudomallei isolates exhibited susceptibility of 96.3% (CLSI) and 97.6% (EUCAST) towards co-trimoxazole in vitro. Broth microdilution results suggested that several isolates were resistance to sulfamethoxazole and trimethoprim separately, which interestingly does not affect their susceptibility towards co-trimoxazole. Analysis of the MIC results reaffirms the significance of the CLSI guideline for antibiotic susceptibility testing and antimicrobial resistance surveillance in Sarawak. It is hoped that results from this study provide reassurance to clinicians in Sarawak that the use of co-trimoxazole is indeed effective for the treatment of melioidosis. Findings of this study warrants further characterization on the molecular and genetic basis of the isolates’ resistance towards both sulfamethoxazole and trimethoprim.